Political entrepreneurship and the Ko-P phenomenon in Taiwan’s democratization* - Yan H. (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Taiwan’s economic modernization and political democratization after World War II have been praised as good examples for emerging countries. As of 2014, Taiwan has successfully gone through four direct presidential elections and two rounds of peaceful transfer of power. However, continuing sectarian quarrels between the ruling Kuomintang and the opposition Democratic Progressive Party cast doubt on the suitability of democracy for a Confucian society. This pessimism is challenged by the emergence of a new political star. A political novice, Ko Wen-je (aka Ko-P), won a landslide victory in the 2014 Taipei mayoral election, which is seen as a phenomenon. It has significant political implications and has so far inspired changes in the political landscape. The adoption of entrepreneurial strategies, such as identifying problems, leading by example, and team creation, are unprecedented in Taiwan’s political campaign. The Ko-P phenomenon demonstrates a self-correcting mechanism in Taiwan’s political system and bodes well for the future of new democracies, particularly for the Greater China Region.